Pendampingan Anak Anak SD (Prathom) di Acara Perayaan Ulang Tahun Ratu Thailand - Dian Heriantini; Aidil Syah Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Queen Sirikit, the founder of Thailand, is an important figure in the country's history and has made significant contributions to society, education and health. His birthday is celebrated every year on August 12, and Thai people pay tribute to him. The annual Queen Sirikit celebration also takes place at Saengarun Anusorn School Nawarthiwat, where students learn about Queen Sirikit's contribution to the nation and her role in their lives. This event is a fun and educational activity, allowing students to participate in the process of overcoming and integrating into their community. Not only that, students are also taught how to honor a mother and the struggle of a mother to raise, educate and provide the best for her children